Sustainability in industry 4.0 : challenges and remedies - Avikal, Shwetank; Singh, Amit Raj; Ram, Mangey (Mathematical engineering, manufacturing, and management sciences, 2022)
"A large and growing number of manufacturers are realizing substantial financial and environmental benefits from sustainable business practices. To develop more sustainable societies, industries need to better understand how to respond to environmental, economic, and social challenges and transform industrial behavior. The objective of this book is to provide knowledge and accelerate the transition towards a sustainable industrial system. The book will help the industry to raise operational efficiency by reducing costs and waste. It will increase industry respond or reach new customers and increase competitive advantage. It offers innovation, scenario planning, and strategic analysis that goes beyond compliance, as well as case studies and remedies to industry 4.0 challenges. This is a growing area and a lot of industries will benefit from this book. Professionals as well as students will refer to this book to add to their knowledge towards Industry 4.0 and it will also help to develop new ideas and solutions to existing and future problems"--